Translational nanomedicine - Meyers, Robert A. (Robert Allen), 1936- (Advances in molecular biology and medicine., 2020)
"The largest high-level encyclopedia on molecular medicine is now publishing a topical volume on Nanomedicine. The long awaited volume gives a comprehensive overview on nanomaterials in drug delivery, imaging and as therapeutics."--